Correlations between serum and salivary hormonal concentrations in response to resistance exercise - Cadore, E.; Lhullier, F.; Brentano, M.; Silva, E.; Ambrosini, M.; Spinelli, R.; Silva, R.; Kruel, L. (Journal of Sports Sciences, 2008)
The aim of present study was to examine the relationships between serum and salivary values of free testosterone, dehydroepiandrosterone, and cortisol before and after a session of resistance exercise. Twenty-eight healthy men (mean age 40 years, s = 4) participated in the present study. Serum and salivary samples were collected at rest and after a multiple-sets resistance exercise protocol, of approximately 25 minutes duration. Concentrations of free testosterone, dehydroepiandrosterone, and cortisol were measured using radioimmunoassay kits. No significant correlation was observed between serum free testosterone and salivary testosterone (r = 0.22 to 0.26, P > 0.05). Serum cortisol was significantly correlated with salivary cortisol before (r = 0.52, P = 0.005) and after (r = 0.62, P = 0.001) the exercise protocol. Serum and salivary concentrations of dehydroepiandrosterone were significantly correlated before (r = 0.68, P < 0.001) and after (r = 0.7, P < 0.001) exercise. The results of the present study suggest that even under exercise conditions, the salivary values of cortisol and dehydroepiandrosterone can reflect the behaviour of these hormones in blood. However, further studies are necessary to verify if salivary testosterone reflects the behaviour of serum free testosterone during resistance exercise.